THE CHARACTER EDUCATIONAL VALUES AS SEEN IN ANNE BRONTE’S AGNES GREY NOVEL - Putri Nur Rahmadhani; Hazairin Eko Prasetyo (Universitas Sarjanawiyata Tamansiswa, 2019)
There were some reasons why this research was carried out 1) to describe the setting of the novel entitled Agnes Grey and 2) to describe the character educational values reflected in the main character of Agnes Grey novel. The approach of this research was a qualitative study. The object of the research was a novel entitled Agnes Grey written by Anne Bronte. In the process of collecting data, the researcher used document analysis by reviewing some literary books. The data analysis technique was inductive content analysis. After analysing the data, the researcher found that 1) there were three types of settings found in the main character of Agnes Grey novel; they were the setting of place, time, and culture 2) the character educational values in this research consisted ofÂ religiousity, honesty, discipline, hard work, creativity, autonomy, democracy, curiosity, rewarding achievement, love peace, joy of reading, environmental care, social care, and responsibility.